دور التشريع الجنائي في مكافحة التحرش الجنسي الإلكتروني دراسة مقارنة بين الفقه الإسلامي والقانون الكويتي: The Role of Criminal Legislation in Combating Electronic Sexual Harassment: A Comparative Study of Islamic Jurisprudence and Kuwaiti Law - Mohammed Al-Banaq, Abdullah Fares; Al-Nahari, Ameen Ahmed Abdullah Qasem; Mohd Raziif, Nor Fahimah (Jurnal Fiqh, 2025)
This study addresses the problem that conventional criminal classifications have struggled to encompass the rapidly growing forms of electronic sexual harassment, thereby raising the question: How effectively do Islamic jurisprudence and Kuwaiti criminal law deter such offences in the cyber domain? Using an inductive approach to collect legislative texts, an analytical method to examine legal rulings and penalties, and a comparative lens to identify convergences and divergences, the study investigates offences such as violating sexual privacy, soliciting adultery or sodomy, and exposing indecency through electronic means. Findings show that Islamic jurisprudence offers a comprehensive framework rooted in fixed religious sources, distinguishing between hudud (e.g., flogging) and taʿzir (e.g., imprisonment, fines) penalties, whereas Kuwaiti Law relies solely on taʿzir punishments and lacks explicit provisions for several electronic forms of harassment. The study recommends revising Kuwaiti legislation to align with Islamic principles, strengthening international cooperation against cross-border cyber-crimes, and promoting public awareness of ethical online conduct.